Virus culture studies in non-gonococcal urethritis. Issue 2 (March 1964) - Morton, R. S.; Gillespie, E. H.; Wilson, M. A.
Abstract : Specimens of urethal discharge and scrapings of the urethra from 45 men with non-gonococcal urethritis have been studied for virus content. Human amnion and monkey kidney cell cultures were inoculated. Various temperatures of incubation were used. Specimens were also inoculated into the yolk sac of seven-day fertile eggs. No cytopathic changes were detected in any specimen examined after direct incubation or after passage. No elementary bodies were seen in stained sections of yolk sacs. Haemagglutination and haemadsorption tests were negative. Paired sera from 21 cases were available for antibody titre study. Estimations of urethral temperature and p H were made. The cause of non-gonococcal urethritis remains to be discovered.